Highly oxygenated and rearranged limonoids from the stem barks of Entandrophragma utile. (April 2020) - Hu, Ya-Lin; Tian, Xiao-Meng; Wang, Cheng-Cheng; Olga, Quasie; Yan, Dan; Tang, Peng-Fei; Zhang, Li-Na; Luo, Jun; Kong, Ling-Yi
Abstract: Seventeen highly oxygenated and rearranged limonoids, including nine previously undescribed phragmalin-type limonoids with 1, 8, 9- and 8, 9, 30-orthesters (entanutilins C–K, 1 –9 ), three undescribed limonoids with rare rearranged-6/6/7/5 skeleton (entanutilins L-N, 10 –12 ), and 5 known limonoids, were isolated from the stem barks of Entandrophragma utile from Ghana (Africa). Their structures including absolute configurations were elucidated based on comprehensive spectroscopic analyses, such as HRESIMS, 1D/2D-NMR, CD exciton chirality method, time-dependent density functional theory (TDDFT)/ECD calculations, and single-crystal X-ray diffraction. Bioactivity screenings suggested that some of these compounds effectively reversed resistance in MCF-7/DOX cells at a nontoxic concentration of 30 μ M with 6- to 19-fold enhancing effects. Graphical abstract: Image 1 Highlights: Twelve undescribed highly oxygenated and rearranged limonoids were isolated from Entandrophragma utile. Their structures were elucidated by NMR, CD exciton chirality, ECD calculations, single-crystal X-ray diffraction. Four compounds effectively reversed resistance in MCF-7/DOX cells.